'ASIA' - Autoimmune/inflammatory syndrome induced by adjuvants: even and odd - G. Valesini; C. Alessandri; C. Perricone (PAGEPress Publications, 2011)
Recently, Shoenfeld and Agmon-Levin described a potential new syndrome, namely ASIA - autoimmune/inflammatory syndrome induced by adjuvants, that comprises four medical conditions: siliconosis, the Gulf war syndrome, the macrophagic myofasciitis syndrome and post-vaccination phenomena, characterized by hyperactive immune responses accompanied by a similar complex of signs and symptoms. Most relevantly, these conditions share a linkage represented by adjuvants. This common soil may possibly induce autoimmune or auto-inflammatory diseases in humans as it was demonstrated in different animal models. Reconsidering under a unified umbrella this apparently detached condition is not only intriguing, but also provocative, and may help in unraveling novel pathogenetic mechanisms, preventive measures, and therapeutic targets.